Evaluasi Program Pendamping Youth Employment di Kecamatan Cilingcing Dari Wahana Visi Indonesia (Jurnal Ilmu Kesejahteraan Sosial, 2018)
This research describes the evaluation of Youth Employment Program of Wahana Visi Indonesia as well as the factors that supports and obstructs the program in achieving its objectives (Case Study in Cilincing Sub-district, North Jakarta). This research was conducted with qualitative approach. The type of research is Sumatif Evaluation Research which aims to obtain information for program implementors about whether the program is worth continuing or has the potential to be applied in different contexts. The results of this study indicate that, Youth Employment program conducted by Wahana Visi Indonesia in Cilincing Sub-district has succeeded in achieving its goal to “Sustained improvement to household income to improve children’s well being. This can be seen from the field findings, that most of the informants in this stud are already working and have a steady income that contributes to the increase in family income. However, if the program is to replicate in a different context, it is necessary to make improvements in several areas, such as in the Assessment and Preparation.